How International Students’ Acculturation Motivation Develops over Time in an International Learning Environment: A Longitudinal Study - Aladegbaiye, Adedapo Tunmise; de Jong, Menno D.T.; Beldad, Ardion D. (Journal of International Students, 2021)
This research investigates how the acculturation motivation (AM) of new international students develops over time, and which factors play a role in this development. In the context of a Dutch university, we interviewed 25 students from 17 countries three times over eight months. The findings show that initial AM levels can be categorized as high or low. These AM levels evolved into four patterns in the three interview rounds: high-low-low, high-low-high, low-highlow, and low-high-high. After four months, twelve factors emerged as affecting the development of students’ AM levels. Prominent factors were prior international experience, language issues, and perceived student identities. After eight months, seven additional factors contributed to subsequent changes in students’ AM levels, including the perceived international learning environment, friendship networks, and teachers’ role in intercultural contacts. Findings suggest that universities can introduce interventions which could improve international students’ acculturation experiences at specific times.